2021
DOI: 10.3390/s21020482
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Combined Transmittance/Fluorescence Leaf Clip Sensor for the Nondestructive Determination of Nitrogen Status in White Cabbage Plants

Abstract: The correct fertilization of vegetable crops is commonly determined on the basis of soil and plant costly destructive analyses, demanding more sustainable non-invasive optical detection. Here, we tested the ability of the combined transmittance/fluorescence leaf clip Dualex device for determining the nitrogen (N) status of cabbage plants. Fully developed leaves from plants grown under different N rates of 0; 100; 200; 300 kg N ha−1 in 2018 and 2019 were measured in the field by the Dualex sensor twice a year i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A similar strategy has been also applied in the set-up of a portable leaf clip-based device has been also set-up for the indirect, nondestructive assay of nitrogen in cabbage leaves, though the measurement of chlorophyll fluorescence. In fact, a correlation has been found to occur between the content of nitrogen in leaves and the ratio between the chlorophyll fluorescence signals measured under excitation at 650 nm and 365 nm, two wavelengths respectively unaffected or absorbed by flavonols and anthocyanins [42].…”
Section: Figurementioning
confidence: 99%
“…A similar strategy has been also applied in the set-up of a portable leaf clip-based device has been also set-up for the indirect, nondestructive assay of nitrogen in cabbage leaves, though the measurement of chlorophyll fluorescence. In fact, a correlation has been found to occur between the content of nitrogen in leaves and the ratio between the chlorophyll fluorescence signals measured under excitation at 650 nm and 365 nm, two wavelengths respectively unaffected or absorbed by flavonols and anthocyanins [42].…”
Section: Figurementioning
confidence: 99%
“…Ouzounis et al [63] confirmed the high correlation of the flavonol index determined with Dualex Scientific+ with the concentrations of flavonoids such as rutin and quercetin determined with the HPLC technique. Tremblay et al [64], Padilla et al [65], Agati et al [66], and Kaniszewski et al [67] confirmed the high correlation of the NBI index with the nutritional status of plants with respect to nitrogen.…”
Section: Chlorophyll Flavonol and Nitrogen Balance Indicesmentioning
confidence: 87%
“…It has also been shown that a high C/N ratio in plants stimulated the production of flavonoids, whereas a low C/N ratio inhibited their production [72]. In a study with cabbage [67], it was demonstrated that the chlorophyll index Our observations are generally consistent with the results of other authors relating to the various genotypes of lettuce, which indicate that blue light has a significant impact on the synthesis of bioactive compounds, including flavonoids [10][11][12]20,66,68]. In the case of red-leaf lettuce, supplementation of white light or red light with blue light has stimulated leaf pigmentation and the synthesis of secondary metabolites [27].…”
Section: Chlorophyll Flavonol and Nitrogen Balance Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-destructive detection of epidermal flavonols by the Dualex and Multiplex devices was also used to define an indicator of leaf nitrogen status, superior to those based on the detection of chlorophyll alone, as proximal sensing of the leaf nitrogen content on turfgrass 5 , cabbage crops 6,7 and ornamental plants 8 and proposed to drive precision fertilization.…”
Section: Chlorophyll Fluorescence Excitation Screening Methodsmentioning
confidence: 99%